Electrochemical mineralization of uric acid with boron-doped diamond electrode: Factor analysis and degradation mechanism. (December 2019) - Liu, Min; Dong, Jiayue; Shen, Yawen; Zhang, Chunyong; Fu, Degang
Abstract: In the present study, the mineralization performance and pathway of uric acid (UA) on boron-doped diamond (BDD) anodes were investigated. The oxidation behavior of UA on BDD surface was firstly tested through cyclic voltammetry measurements. The individual and joint effects of four quantitative parameters (applied current density, NaHCO3 concentration, NaCl concentration and flow rate) on UA mineralization were then examined with Doehlert experimental design. The results acquired by statistical analysis revealed that NaCl concentration and applied current density displayed the most dominant roles on UA degradation, while the influences of NaHCO3 concentration and flow rate were statistically insignificant. As a result, the following optimal conditions were reached: applied current density of 7.80 mA cm −2, NaHCO3 concentration of 6.0 mM, NaCl concentration of 9.0 mM and flow rate of 600 mL min −1, which gave a TOC decay of 89.4%, a specific energy consumption of 125.36 KWh kg −1 TOC, a combustion current efficiency of 15.0% and an electrical energy per order of 35.79 KWh m −3 order −1 within 30 min of electrolysis. Further results from LC/MS analysis confirmed the ring rupture of UA during the electrolysis, due to the attack of hydroxyl radicals and active chlorine species. Accordingly, two plausible degradation pathways of UA in bicarbonate and chloride media on BDD anode were proposed respectively. Graphical abstract: Image 1 Highlights: Boron-doped diamond is employed to mineralize uric acid. Doehlert design can successfully optimize the operating parameters involved. The mineralization of uric acid is favored in the presence of chloride. Uric acid mineralization routes in NaHCO3 and NaCl media are proposed.